ECOTOURISM DEVELOPMENT STRATEGY DALAM UPAYA PENINGKATAN PEREKONOMIAN MASYARAKAT LOKAL: STUDI KASUS PENANGKARAN HIU KARIMUNJAWA, JAWA TENGAH - Kharisma, Nazwatul; Oktaviah, Yufenti; Erwantiningsih, Eni (Bhinneka Multidisiplin Journal, 2025)
Indonesia, with its rich marine resources and more than 17,000 islands, has enormous tourism potential. The ecotourism sector, in particular, is spearheading inclusive economic growth and strengthening Indonesia's image as a leading global destination. Ecotourism is defined as responsible nature-based tourism activities focused on education, natural resource conservation, and, crucially, increasing local community incomes. This research focuses on the Karimunjawa Shark Sanctuary as a relevant case study. This shark sanctuary, a family initiative launched in 2019, seeks to transform the perception of sharks from mere objects of consumption to sustainable tourism assets, while preserving their habitat. By optimizing local resources and a construction concept predominantly using wood, the sanctuary offers an interactive educational experience with a variety of marine life.This shark sanctuary has significant potential to become a new economic powerhouse, creating opportunities for local fishermen to become educational guides, housewives to produce eco-friendly souvenirs, or young people to manage homestays, thus transforming into a catalyst for ecotourism development strategies that support community empowerment and well-being. This study aims to analyze the ecotourism development strategy of the Karimunjawa Shark Sanctuary to improve the local economy. The method used is a descriptive qualitative approach using the 4A concept (Attraction, Accessibility, Amenities, Ancillary services)